Development of the Urinary Tract in Fetal Rats: A Micro-CT Study - Wille, Stephanie; Peukert, Nicole; Haak, Rainer; Riedel, Jan; Mayer, Steffi; Kluth, Dietrich; Lacher, Martin; Gosemann, Jan-Hendrik; Markel, Moritz (European Journal of Pediatric Surgery, 2022)
Introduction Micro-computed tomography (micro-CT) is an established tool to study fetal development in rodents. This study aimed to use micro-CT imaging to visualize the development of the urinary tract in fetal rats.Materials and Methods Fetal rats from embryonic day (ED) 15, ED17, ED19, ED21, and N0 (newborn) (n = 6 per group; 3 males) were fixed and desiccated using the “critical point” technique. We utilized the micro-CT system (SkyScan) and analyzed the resulting scans with CTAn, DataViewer, and ImageJ to visualize the morphology and quantify the volumes of kidney, bladder, adrenal gland, as well as length of the ureter.Results High-resolution micro-CT showed continuous growth of both kidneys from ED15 to N0, with the highest increase between ED19 and ED21. The length of the ureter increased from ED15 to ED21 and remained stable until birth. The volume of the bladder steadily increased from ED15 to N0.In females, a statistically higher volume of the adrenal gland on ED21 was observed, whereas no sex-specific differences were seen for kidney, ureter, and bladder development.Conclusion Micro-CT depicts an excellent tool to study urinary tract development in the fetal and neonatal rat. It enables the metric quantification of longitudinal anatomic changes in high definition without previous destructive tissue preparation. The present study revealed sex-specific differences of the adrenal gland development and provides comprehensive data for the understanding of fetal urinary tract development, inspiring future research on congenital urological malformations.
Keywords: micro-CT; kidney development; adrenal gland development; ureter development; bladder development